The O4f + O6V eclipsing binary system Sk‒67°105 in the Large Magellanic Cloud - Ostrov, Pablo Gabriel (2003)
We present a new V light curve of the early type Magellanic eclipsing binary Sk-67°105, based on charge-coupled device images obtained at CASLEO. We perform an analysis of our data, together with published radial velocities, deriving the following masses and radii: M1 = 48.3 M⊙, R1 = 16.9 R⊙ for the O4f component and M2 = 31.4 M⊙, R2 = 13.8 R⊙ for the O6 component. We found that this system is the brightest member of a tight star cluster, belonging to an OB association.